2019
DOI: 10.1371/journal.pone.0215786
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of chest ultrasound in children with cystic fibrosis – Pilot study

Abstract: Cystic fibrosis (CF) is one of the most common genetic disorders among the White population. The disease has a progressive course and leads to a reduction in the quality of life and of life expectancy. Standard diagnostic procedures used in the monitoring of CF patients include methods which expose patients to ionizing radiation. With increasing life expectancy in CF the cumulative dose of ionising radiation increases, prompting clinicians’ search for safer imaging studies. Despite its safety and availability … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 38 publications
(50 reference statements)
3
30
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is another modality that has recently been proposed for life-long imaging surveillance of CF patients, with the advantage of lacking ionizing radiation [ 10 ]. Ultrasound is currently the most commonly used imaging technique; therefore, lung ultrasound (LUS) can be an important tool in the evaluation of children with CF having multiple advantages, including availability, cost-effectiveness, non-invasiveness, safety, and bedside usability in critically ill patients [ 11 , 12 ]. In the current study, we aimed to determine the diagnostic performance of LUS in the evaluation of CF pulmonary exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is another modality that has recently been proposed for life-long imaging surveillance of CF patients, with the advantage of lacking ionizing radiation [ 10 ]. Ultrasound is currently the most commonly used imaging technique; therefore, lung ultrasound (LUS) can be an important tool in the evaluation of children with CF having multiple advantages, including availability, cost-effectiveness, non-invasiveness, safety, and bedside usability in critically ill patients [ 11 , 12 ]. In the current study, we aimed to determine the diagnostic performance of LUS in the evaluation of CF pulmonary exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…Lower-frequency transducers are used for older children and overweight or obese adolescents ( Lovrenski et al, 2016 ). Curved array transducers are used to insonate between ribs, below the diaphragm, or from the suprasternal notch ( Joshi et al, 2019 ; Strzelczuk-Judka et al, 2019 ).…”
Section: Technique and Methods Of Scanningmentioning
confidence: 99%
“…The presence of interstitial syn-drome may indicate the presence of fluid in the interstitial space (for instance, in pulmonary fibrosis) or inflammatory infiltrate within this space (fig 1). In paediatric patients, this syndrome most often occurs in the course of lower respiratory tract infections (especially viral pneumonia), acute respiratory distress syndrome, cardiogenic pulmonary oedema, hyperhydration of patients receiving haemodialysis, interstitial lung disease, cystic fibrosis and post-obstructive pulmonary oedema [4][5][6][7].…”
Section: Interstitial Syndromementioning
confidence: 99%
“…A study suggested the presence of B lines were typical for small bronchiec-tasis [68], but it has been demonstrated that B line profile lacks specificity as they are seen in several diseases including interstitial inflammation and fibrosis [69]. It has been stated that a good correlation exists between LUS, expressed by an adapted bronchiolitis score [13] and chest X-ray evaluated by a modified Crispin Norman score, highlighting that, given the variability of the diseases described by B lines, it would be inadequate to make the diagnosis of CF lung only by ultrasound [6]. A small study compared a LUS score (evaluating only the presence of consolidation and B-lines pattern) with the modified Bhalla CT score and showed a correlation between the two methods and some partial correlation with the lung function expressed by FEV1 and FVC [70].…”
Section: Cystic Fibrosismentioning
confidence: 99%